Interaction of PPO-inhibitor herbicide mixtures and mechanistically studies thereof - Menzani, Ana Paula Meirelles (2017)
Crop production provides the food and fiber necessary to sustain the world\'s population. Effective weed management is critical to maintaining agricultural productivity. Intensive or continuous use of herbicides that act on the same target site, or are detoxified by similar processes within crops and target weeds frequently results in the development of weeds resistant to a specific herbicide or class of herbicides. Weed resistance due to the extensive use of glyphosate in glyphosate tolerant crop systems has become one of the most serious issues facing agriculture today. Thus PPO-inhibitor herbicides are an alternative mechanism of action that have the potential to mitigate the development of resistant weeds in weed control systems where crop tolerance is sufficient to allow them to be effectively deployed. While there are few reports of weed resistance to PPO-inhibitor herbicides it has not developed to the extent that it is a commercial problem for growers. When used at recommended doses, they typically have favorable regulatory profiles. Furthermore, most of them are highly compatible with no-tillage agriculture. However, PPO-inhibitor herbicides are typically more active on dicots than monocots. This thesis provides information with regards to effectiveness of certain binary mixtures of PPO herbicides as weed control agents. The mixtures showed synergistic effects and could control monocots as Echinochloa crus-galli and volunteer corn besides control the dicots species. Regarding the compounds studied, trifludimoxazin and flumioxazin required less amount of compound to inhibit 50% of PPO2 activity in all plants species tested, while sulfentrazone and saflufenacil, one of the best mixtures in the field, showed that needed bigger concentrations to inhibit 50% of the PPO2 compared to other compounds evaluated.The absorption and translocation of these compounds individually or in mixtures, showed that as single compounds, the absorption was slower in maize than E. crus-galli and there was no difference among the herbicides except trifludimoxazin, that was significantly lower than the other compounds. Saflufenacil was the herbicide that showed the best translocation out of treated leaf point, while trifludimoxazin has not shown any translocation out of leaf treated. In mixtures, the compounds showed some differences in absorption and translocation, which it was variable according to species studied. Some traits of PPO-tolerant were also evaluated in Arabidopsis thaliana which indicates potential traits to be developed in crops of interest.